The Impact of Ideological Education in University Sports on Students’ Resilience - Guoqiang Li (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
To explore the impact of ideological and political education in extracurricular sports activities in universities on students' resilience to setbacks. This article uses the POMS (Profile of Mood States) measurement tool to select 120 college students with high total negative emotional disorder scores (TMD) as the experimental subjects and conducts a 4-month physical exercise guidance experiment on them. The research results show that there are significant differences in various indicators of psychological impact between male and female students in different sports events. Especially in terms of psychological factors such as tension, anger, fatigue, and self-esteem, there are significant differences between male and female students. This may be related to male students preferring to choose basketball or martial arts events, while female students are more inclined to choose physical training and martial arts events. Based on the comprehensive research results, the following conclusion can be drawn planned, organized, and regular sports activities have an effective effect on improving the psychological quality of college students. Sports activities can help students cultivate a resilient and positive mindset, enhancing their resistance to setbacks and difficulties. However, research has also found that gender differences have differences in the psychological impact of sports activities on college students. Different sports may have different psychological impacts on male and female students. Therefore, when carrying out ideological and political education in sports activities, it is necessary to fully consider gender differences and provide students with sports that are suitable for their personality and needs.